(untitled) (Revista de Investigaciones Universidad del Quindío, 2020)
The main objective of eBranding or Branding Digital strength of the future, to know where digital communication is going, the business opportunities it entails for companies, the role of eBranding in this new context, has a qualitative approach with explanatory correlate scope, a non-experimental design where companies participate pretending to have network visibility obtaining a greater benefit for the company, meeting the expectations of users taking care of their online reputation, having as their mission to translate the lifestyle that brands, in this way, see the benefits as a new form of management in the use of digital media, where you can see that other corporate and high-tech content is highlighted by eBranding. Today in a world without borders, where technology copies up people’s DNA, branding is a must in the management of all businesses.